A single residue in influenza virus H2 hemagglutinin enhances the breadth of the B cell response elicited by H2 vaccination - Andrews, Sarah F.; Raab, Julie E.; Gorman, Jason; Gillespie, Rebecca A.; Cheung, Crystal S. F.; Rawi, Reda; Cominsky, Lauren Y.; Boyington, Jeffrey C.; Creanga, Adrian; Shen, Chen-Hsiang; Harris, Darcy R.; Olia, Adam S.; et al. (Nature medicine, 2022)
Conserved epitopes on the influenza hemagglutinin (HA) stem are an attractive target for universal vaccine strategies as they elicit broadly neutralizing antibodies. Such antibody responses to stem-specific epitopes have been extensively characterized for HA subtypes H1 and H5 in humans. H2N2 influenza virus circulated 50 years ago and represents a pandemic threat due to the lack of widespread immunity, but, unlike H1 and H5, the H2 HA stem contains Phe45 HA2 predicted to sterically clash with HA stem-binding antibodies characterized to date. To understand the effect of Phe45 HA2 , we compared the HA stem-specific B cell response in post hoc analyses of two phase 1 clinical trials, one testing vaccination with an H2 ferritin nanoparticle immunogen ( NCT03186781 ) and one with an inactivated H5N1 vaccine ( NCT01086657 ). In H2-naive individuals, the magnitude of the B cell response was equivalent, but H2-elicited HA stem-binding B cells displayed greater cross-reactivity than those elicited by H5. However, in individuals with childhood H2 exposure, H5-elicited HA stem-binding B cells also displayed high cross-reactivity, suggesting recall of memory B cells formed 50 years ago. Overall, we propose that a one-residue difference on an HA immunogen can alter establishment and expansion of broadly neutralizing memory B cells. These data have implications for stem-based universal influenza vaccination strategies. A bulky residue in the stem domain of the influenza virus H2 hemagglutinin appears pivotal in eliciting broadly cross-reactive antibodies capable of recognizing diverse group 1 influenza subtypes and is informative for universal influenza vaccine development.